Answered

11 + (3)(9) Step 1: 11 + (9)(3) Step 2: (11 + 9)(3) Step 3: 20(3) Step 4: 60 Analyze the work to find the error.

Answer :

Answer:

Step 2 is where this person went wrong

Step-by-step explanation:

Should be

11 + (9)(3)= x

11 + 27= x

x = 38

cool1212

Answer:

Step 2 is where the error started. You can see the person did the order of operations wrong. The person was supposed to multiple (9)(3) first because of PEMDAS; (9)(3)=27 and then you add the 27 to 11 and get 38

Step-by-step explanation:

Other Questions